Implementasi Teori Subjective Expected Utility Studi Kasus: Pekerja Perempuan Korban Pelecehan Seksual - Tasha Amalia Surbakti; FX Sugiyanto (Jurnal Wanita dan Keluarga, 2022)
Industrial revolution in 18th century made women has have to adapt from home industry to modern manufacture. These change made women have to face social problems from the “women better stay at home” stigma to workplace discriminations, that later effect women either from psycologichal side and also socio-economics side. This paper specifically choosse one of those problems, which is sexual harassment in the workplace and saw the effects through economics point of view. With emotions, types of harassments, self efficacy, knowledge, and socio-economics as independent variables, this paper try to aim the main reason of Jabodetabek’s women worker preference changed after sexual harassment in the workplace with linear regression and descriptive analysis as the analythical method. The results were showed that the respodents preferences changed after the effect of emotions pressure at work and problem with self efficacy rathter than socio-economics pressure and types of sexual harassment that happened to them before.